The Transcendence revives through the Immanence: An Examination on Existential crisis in selected texts of Fyodor Dostoevsky, Franz Kafka and Milan Kundera - Haque, Sumaiya Tasneem (BRAC University, 2012)
This thesis paper is submitted in a partial fulfillment of the requirement for the degree of Bachelor of arts in English and Humanities